Still SDAPing Along: 20 Years of the Structural Database of Allergenic Proteins - Schein, Catherine H.; Negi, Surendra S.; Braun, Werner (Frontiers in Allergy, 2022)
The introduction of plant extracts to mitigate the symptoms of “hay fever”, about a century ago, led to discoveries beginning sixty years ago on determining the sequences and eventually structures of allergenic proteins. As more proteins were cloned, there was a need to rapidly identify and categorize those with significant similarity to known allergens. The Structural Database of Allergenic Proteins (SDAP) was created at the beginning of the 21st century as the first cross-referenced website to allow rapid overview of the structures and sequences of allergenic proteins. SDAP provides a way to identify sequence and functional similarities between these proteins, despite the complex nomenclature system based on the Latin names of their different sources. A rapid FASTA search simplifies grouping allergens from the same structural or functional family. SDAP also provides an overview of the rapidly expanding literature on the sequence, structure and epitopes of allergenic proteins and a way to estimate the potential allergenicity of novel proteins based on rules provided by the IUIS. Twenty years and a pandemic later, the list of allergenic proteins and their attributes continues to grow. SDAP is expanding and improving to allow rapid access to all this information.